한·중 FTA가 제주 감귤 생산액과 관련 전후방산업에 미치는 파급효과 분석 - 전익수 (한국농촌경제연구원, 2013)
This study analyzed the economic impacts of Korea-China FTA on the citrus industry of Jeju Province. As for the impact analysis of Korea-China FTA, the agricultural partial equilibrium model `KREI-KASMO 2011' and a regional input-output model were used to measure the economic impact of the free trade agreement on the citrus fruit industry and the local industry of Jeju. The results showed that if the free trade agreement took effect in 2013, the total amount of decrease in citrus production for the following ten years was estimated to be a maximum of 1,597 billion won. Based on the decrease of the citrus industry, the regional input-output model showed that its impact on the local industry during the next ten years would amount to as much as 3,109 billion won. By regions, direct effect on Jeju was bigger than on other regions, but indirect effect and induced effect were not as big as on other regions. By industrial sectors of Jeju, the impact on the service industry was bigger than on the manufacturing sector. The countermeasures to cope with the Korea-China FTA were also suggested in the aspects of negotiation strategy and industrial strategy.
Keywords: 한∙중 FTA; 농업부문 전망모형; 지역산업연관분석; 제주 감귤산업; Korea-China FTA; KREI-KASMO 2011; regional input-output model; citrus industry of Jeju